Does oil price matter for the Malaysian stock market? - Bani, Yasmin; Ramli, Siti Noraini (Kulliyyah of Economics and Management Sciences, International Islamic University, 2019)
Uncertainty in the crude oil price has motivated researchers to analyze the relationship between oil prices and economic activities. In recent years, the literature has changed focus of the relationship to asset prices such as stock and gold prices. This paper investigates the effect of oil prices on Malaysian stock prices. We use monthly data for the period 2007-2016 and utilize the Auto Regressive Distributed Lag (ARDL) cointegration approach to estimate the short-run and long-run relationship between crude oil price and two different indices; namely FBMKLCI and FBMEMAS. We find that crude oil prices are cointegrated with both indices and the relationship is negative and significant in the long-run. This is consistent with theoretical expectations and existing empirical studies.